2022
DOI: 10.26522/brocked.v31i2.915
|View full text |Cite
|
Sign up to set email alerts
|

Education for Sustainable Development (ESD) Infusion into Curricula: Influences on Students’ Understandings of Sustainable Development and ESD

Abstract: Formal education for sustainable development (ESD) is in large part dependent on capacity-building and training of teachers as they are the individuals who must both deliver ESD at the classroom level as well as utilise their own knowledge, values and skills in support of sustainability. In this research, teacher educators within a higher education institution in Jamaica undertook a collaborative action research project to infuse ESD into their selected undergraduate and postgraduate courses during the spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In this context, facilitation methods play a crucial role due to their potential to enhance the internal mechanisms of personal development and selfimprovement for each participant in the educational process. Facilitative methods enable the IJSHE 25,4 teaching of sustainable development through practical application scenarios, thereby helping students overcome challenges and make independent decisions in the interest of sustainable development (Ferguson et al, 2022;Reeves, 2019).…”
Section: The Role Of Facilitation Methods In Sustainable Development ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, facilitation methods play a crucial role due to their potential to enhance the internal mechanisms of personal development and selfimprovement for each participant in the educational process. Facilitative methods enable the IJSHE 25,4 teaching of sustainable development through practical application scenarios, thereby helping students overcome challenges and make independent decisions in the interest of sustainable development (Ferguson et al, 2022;Reeves, 2019).…”
Section: The Role Of Facilitation Methods In Sustainable Development ...mentioning
confidence: 99%
“…It has been widely acknowledged that interdisciplinary education plays a crucial role in equipping students with a comprehensive understanding of the theory and development of knowledge in the field of SD (Cairns et al , 2020; Cirella and Russo, 2019). By embracing an interdisciplinary approach, students are able to foster a balanced perspective on sustainability (Braßler and Sprenger, 2021) and cultivate the ability to collaborate effectively in interdisciplinary teams, thereby generating innovative ideas essential for achieving the SDGs (Ferguson et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Higher education institutions are at the end of the formal education cycle, and as such, they play a crucial role in bridging gaps and furthering ESD by equipping students with the competencies and skills necessary to drive pro-environmental change in their lives and future workplaces (Filho et al , 2017; Lozano, 2006; Zilahy and Huisingh, 2009). Incorporating ESD into academic curricula is a difficult task that is largely dependent on the preparedness, expertise and creativity of university teaching staff (Ferguson et al , 2022). Adequate training is required to prepare university instructors to develop a holistic approach to ESD by adopting appropriate content and using teaching methods that correspond to the profiles of contemporary university students (Barth and Rieckmann, 2012; Ferguson et al , 2022; Lozano, 2010), as well as through cooperation with colleagues from higher education institutions in other countries (Leicht et al , 2016).…”
Section: Education For Sustainable Developmentmentioning
confidence: 99%
“…Incorporating ESD into academic curricula is a difficult task that is largely dependent on the preparedness, expertise and creativity of university teaching staff (Ferguson et al , 2022). Adequate training is required to prepare university instructors to develop a holistic approach to ESD by adopting appropriate content and using teaching methods that correspond to the profiles of contemporary university students (Barth and Rieckmann, 2012; Ferguson et al , 2022; Lozano, 2010), as well as through cooperation with colleagues from higher education institutions in other countries (Leicht et al , 2016). A case study with university teachers from 10 European countries revealed that web-based seminars could be an effective medium for sharing expertise, experiences and ideas, as well as for training university instructors on how to integrate ESD into their courses (de Kraker et al , 2017).…”
Section: Education For Sustainable Developmentmentioning
confidence: 99%
“…ESD is a learning approach based on the principle of sustainability (Mochtar et al, 2014) which is designed to develop knowledge, skills (Ali, 2017) attitudes to maintain the environment so that it can support the needs of future generations (Wilujeng et al, 2019). ESD can be implemented through the implementation of learning in tertiary institutions (PT) (Mkumbachi et al, 2020) because it can become an arena for meetings between individuals and significant sustainability with critical thinking, provocative questions, and alternative ideas to find a better environment (Ferguson et al, 2022). especially in chemistry study programs, according to Burmeister et al (2012), chemistry is considered to have a central role in ESD.…”
Section: Introductionmentioning
confidence: 99%